PREVALENCE, MANAGEMENT, AND OUTCOME OF RESISTANT HYPERTENSION IN PEOPLE WITH CKD : A COMPREHENSIVE SYSTEMATIC REVIEW - Sijabat, Landong; Novettiandari, Guinanti (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Patients with chronic kidney disease (CKD) are susceptible to resistant hypertension, which is a serious problem. Patients should take into account reversible causes as the prevalence of this ailment is difficult to ascertain. Its development is influenced by the renin-angiotensin-aldosterone system and the sympathetic nervous system. The efficacy of current hypertension treatments, such as medication and lifestyle modifications, in treating resistant hypertension is low. Recent studies have shown a reduction in blood pressure equivalent to that of a single antihypertensive drug in less severe cases of hypertension. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. The literature was assembled using a variety of online databases, including ScienceDirect, PubMed, and SagePub. Result: The study screened about 3.000 publications using reputable sources including Science Direct, SagePub, and PubMed. Five papers were found to be pertinent for systematic investigation, after which the entire material was examined in more detail. Conclusion: It has been demonstrated that patiromer, a K1-binding drug, improves cardiovascular outcomes in patients with hypertension and chronic kidney disease (CKD). Phase II trial results demonstrated that patiromer can safely permit spironolactone use and prevent hyperkalemia, hence reducing renin-angiotensin-aldosterone system inhibitor non-use in patients with heart failure refractory to exercise. Long-term findings regarding the effects on the kidneys and heart are nevertheless required. Treatment for renal denervation has demonstrated encouraging outcomes in lowering blood pressure without side effects.